Actividad catalítica de complejos de rodio (I) con ligandos bidentados a base de fósforo en reacciones de hidroformilación de limoneno (2007)
We have prepared the com¬plexes RhCl(dppe)2, RhCl(dppp)2 and RhCl(dppb)2, where dppe = diphenylphosphinoethane; dppp = diphenylphosphinopropane; dppb = diphenylphosphinobutane. The above complexes were used as catalytic precursor in the hydroformylation of limonene at differents concentrations and temperatures. It has found that the best catalytic precursor was the Rhodium complex with dppb as ligand it seems that the P-Rh-P angle is very important in substrate activation